Control contable COSO II, para el Control Contable financiero en el Gobierno Autónomo Descentralizado Parroquial Rural de la Magdalena, en el primer semestre del año 2023 - Guevara Mayorga, Narcisa Elizabeth (2024)
The Decentralized Rural Parochial Autonomous Government of La Magdalena located in the Chimbo Canton, Bolívar Province, does not have an internal control system, therefore, a series of problems were evident that affect the efficiency of the institution's management, for example. which is essential to manage a tool such as COSO II, for financial accounting control, in which it was determined as a general objective; improve financial accounting control in the Rural Parochial Decentralized Autonomous Government of La Magdalena through the application of a Coso II model. In the methodological aspect, exploratory, bibliographic, descriptive research was used, presenting a qualitative approach, from this perspective the following is concluded; The diagnosis reveals that the Decentralized Rural Parochial Autonomous Government of La Magdalena faces important challenges in terms of financial accounting control. However, it also represents a valuable opportunity to implement corrective measures and strengthen its capacity for accountability and transparency. Finally, a design of a COSO II risk management model is carried out for the financial accounting control procedure of the Rural Parochial Decentralized Autonomous Government. of La Magdalena, is a strategic and proactive measure that will strengthen financial management.